Judicial decisions on the law of international organizations - Ryngaert, Cedric; Dekker, I. F.; Wessel, Ramses A.; Wouters, Jan, 1964- (Oxford, United Kingdom : Oxford University Press, 2016)
"With the rising relevance of international organizations in international affairs, and the general turn to litigation to settle disputes, international institutional law issues have increasingly become the subject of litigation, before both international and domestic courts. The judicial treatment of this field of international law is addressed in Judicial Decisions on the Law of International Organizations through commentary on excerpts of the most prominent international and domestic judicial decisions that are relevant to the law of international organizations, providing in-depth analysis of judicial decisions. The commentaries, which are opinionated and critically engage with the decision in question, are written and edited by leading experts in the field of international institutional law, containing commentators' and stakeholders' reactions to the decisions, as well as subsequent decisions, codifications, and reports"--Unedited summary from book jacket.
Bankovic and Others v. Belgium and 16 other Contracting States, App. No. 52207/99, European Court of Human Rights, 12 December 2001; (Case Concerning Legality of Use of Force (Serbia and Montenegro v. Belgium), Preliminary Objections, Judgment, [2004] ICJ Reports 279) / Tulio Scovazzi -- Bosphorus Hava Yollari Turizm veTicaret Anonim Sirketi v. Ireland, App. No. 45036/98, European Court of Human Rights, 30 June 2005 / Tobias Lock -- Agim Behrami and Bekir Behrami v. France, App. No. 71412/01 and Ruzhdi Saramti v. France, Germany and Norway, App. No. 78166/01, European Court of Human Rights, 2 May 2007 / Santiago Villalpando -- Gasparini v. Italy and Belgium, App. No. 10750/03, Admissibility Decision, European Court of Human Rights, 12 May 2009 / Tobias Lock -- Mukeshimana-Nguilinzira and ors. v. Belgium and ors., Brussels Court of First Instance, ILDC 1604 (BE 2010), 8 December 2010 / Cedric Ryngaert -- Nuhanovic v. Netherlands, Appeal Judgement, LJN: R5388, ILDC 1742 (NL 2011) and Mustafic v. Netherlands, Appeal Judgement, LJN: BR 5386, Dutch Court of Appeals, 5 July 2011 / Otto Spijkers -- Al-Jedda v. United Kingdom, App. No. 27021/08, European Court of Human Rights, 7 July 2011 / Aurel Sari -- Manderlier v. Organisation des Nations Unies and Etat Belge (Ministre des Affaires Etrangeres), Tribunal Civil de Bruxelles, 11 May 1966, Journal des Tribunaux, 10 December 1966, No. 4553, 121 / Pierre Schmitt -- Abdi Hosh Askir v. Boutros Boutros-Ghali, Joseph E. Connor et al., US District Court SDNY, 29 July 1996, 933 F. Suppl. 368 (SDNY 1996) / Tom Ruys -- Difference Relating to Immunity from Legal Process of a Special Rapporteur of the Commission on Human Rights, advisory opinion, [1999] ICJ Reports 62 / Chanaka Wickremasinghe -- Beer and Regan v. Germany, App. No. 28934/95 and Waite and Kennedy v. Germany, App. No. 26083/94, European Court of Human Rights, 18 February 1999 / Thore Neumann and Anne Peters -- League of Arab States v. T., Belgian Court of Cassation, 127 ILR (2005) 94, 12 March / Cedric Ryngaert -- Prewitt Enterprises Inc and ors v Organization of Petroleum Exporting Countries, Appeal judgment, 353 F3d 916 (11th Cir 2003); ILDC 715 (US 2003) / Kirsten Boon -- Entico Ltd. v. UNESCO, [2008] EWHC 531 (Comm) / Chanaka Wickremasinghe -- Western European Union v Siedler, and others, Belgian Court of Cassation, 21 December 2009 / Pierre Schmitt -- OSS Nokalva, Inc. v. European Space Agency, Court of Appeals for the Third Circuit, 617 F.3d 756 (US 3d Cir. 2010) / Kirsten Boon -- Mothers of Srebrenica v. The Netherlands & the UN, LJN: BW1999, Dutch Supreme Court, 13 April 2012 AND Stichting Mothers of Srebrenica and Others against the Netherlands, App. No. 65542/12, European Court of Human Rights, 11 June 2013 / Aleksandar Momirov.
Includes bibliographical references and index.
Keywords: International agencies -- Law and legislation -- Cases; Judgments; International law; 89.72 international organizations; International agencies -- Law and legislation; International law; Judgments; Trials, litigation, etc